Literasi Matematika Siswa Pendidikan Menengah: Analisis Menggunakan Desain Tes Internasional dengan Konteks Indonesia - Mahdiansyah --; Rahmawati -- (Jurnal Pendidikan dan Kebudayaan, 2014)
The purpose of the study was to measure students’ mathematical literacy achievement at secondary education level on the international test design adjusted to the context of Indonesia, and to analyze factors affecting the achievement. In addition, to conducting test, the survey was also administered to obtain data on the test participant students, maths teachers, and their educational background. Sampling was done by using a multi-stage stratified random sampling. This research revealed that the literacy achievement of students was still low, but the disparity of literacy achievement among cities was varied. Student literacy achievement in Yogyakarta was relatively evenly compared to other cities. Uncertainty and data is the most easily content compared to other mathematical contents. Examined from the aspect of context, scientific is the lowest achieved by students.The test items that measure higher order thinking skills (HOTS) had not been well mastered by students. There are number of determinants of mathematics literacy achievement, namely personal factor, instructional factor, and environmental factor. The conclusion of the study is students’ mathematical literacy at secondary educationlevel was still low, although the design of international test used had been adjusted by the Indonesian context.